The History of Lutheranism from The Perspective of Jan Poszakowski - Żukowska, Justyna (Resovia Sacra, 2021)
The article presents the genesis and spread of Lutheranism in Europe as perceived by the Jesuit and historian Jan Poszakowski. This scholar was the author of several historical and theological works. One of them, entitled The Lutheran History, describes in detail the successive stages of the Reformation movement, specifically Lutheranism, in individual European countries. The author begins his History of Lutheran from the 16th century, but also refers in some fragments of his work to earlier eras, ending with the Thirty Years’ War.